Effectiveness of Surgical Face Masks in Reducing Acute Respiratory Infections in Non-Healthcare Settings: A Systematic Review and Meta-Analysis - Wang, Min Xian; Gwee, Sylvia Xiao Wei; Chua, Pearleen Ee Yong; Pang, Junxiong (Frontiers in Medicine, 2020)
Background: Acute respiratory illnesses (ARI) are the most common respiratory infectious diseases among humans globally. Surgical mask (SM) wearing has been shown to be effective in reducing ARI among healthcare workers. However, the effectiveness of SM in reducing ARI in the non-healthcare settings remains unclear. This review aims to summarise and assess the association between SM wearing and ARI incidence, from existing interventional and observational studies conducted in non-healthcare settings. Methods: Systematic literature searches conducted in PubMed, Cochrane Library, and Embase databases identified 503 unique studies. After screening, 15 studies (5 randomised controlled trials and 10 observational studies) were assessed for reporting and methodological qualities. Proportions of ARI episodes in each group, and adjusted summary statistics with their relevant 95% confidence intervals were extracted. Data from ten observational studies were pooled using the generic inverse variance method. Results: A total of 23,892 participants between 7 to 89 years old involved across 15 studies from 11 countries were involved. Key settings identified were Hajj, schools, and in-flight settings. A modest but non-significant protective effect of SM on ARI incidence was observed (pooled OR 0.96, 95% CI: 0.8-1.15). Subgroup analysis according to age group, outcome ascertainment and different non-healthcare settings also revealed no significant associations between SM use and ARI incidence. Conclusion: Surgical mask wearing among individuals in non-healthcare settings is not significantly associated with reduction in ARI incidence in this meta-review.